Conceptual Model of Inclusive Leadership in Enhancing Employee Engagement in Retail Business - Mahfud (PT. Berkah Digital Teknologi, 2025)
Purpose: Employee engagement is a key factor in the operational success of retail businesses, particularly amidst high employee turnover and customer service pressures. However, many retail companies still rely on hierarchical leadership styles that offer limited participatory space. This conceptual research aims to develop a theoretical model explaining how inclusive leadership can enhance employee engagement through the mediating role of psychological safety. Research Methodology: A systematic literature review was conducted on 11 studies related to human resource management, leadership, and the retail sector (2010–2024). The study integrates Social Exchange Theory and Psychological Safety Theory to build a conceptual framework. Results: The findings propose three key theoretical propositions: 1. Inclusive leadership positively relates to psychological safety in retail environments. 2. Psychological safety mediates the relationship between inclusive leadership and employee engagement. 3. Employee engagement is higher in retail stores with an inclusive culture compared to those with a hierarchical culture. These propositions suggest that inclusive leadership fosters an environment where employees feel safe to engage, leading to greater emotional and cognitive involvement in their roles. Limitations: The study is conceptual and does not provide empirical validation. Future research is needed to test the model through primary data collection, such as surveys or case studies in retail companies. Additionally, the study focuses primarily on frontline employees, and further exploration is needed to include the role of middle management in the process. Contribution: This study contributes to the theoretical understanding of the internal mechanisms of inclusive leadership in the retail sector, with practical implications for the development of human-centric leadership training programs.